Divining without seeds : the case for strengthening laboratory medicine in Africa - Okeke, Iruka N., 1970- (Culture and politics of health care work., 2011)
Infectious disease is the most common cause of illness in Africa, yet health practitioners often fail to identify causative microorganisms in most patients. Iruka Okeke argues that there is a pressing need to improve laboratory diagnostics.